A Frenchman in Search of Franklin : De Bray's Arctic Journal, 1852-54. - De Bray, Emile Frédéric (Heritage., 1992)
A remarkable account by a French naval officer who volunteered to take part in the Royal Navy search for the Franklin expedition.